Re-Thinking of Popular Culture Studies as Interdisciplinary Subject - Pun, Min Bahadur (Tribhuvan University Journal, 2010)
This paper discusses the emergence of popular culture as an interdisciplinary subject of research. The simplest way to define the term 'popular culture's is a culture widely favored by many people. It refers to beliefs, practices and objects widely shared among people. Some of the examples of popular culture are romance novels, science fiction, photography, pop music, journalism, advertising, television, video, computers, Internet, etc. The study of popular culture entered a new phase in the cultural and intellectual history with the establishment of the Center for Contemporary Cultural Studies (CCCS) led by Richard Hoggart and Stuart Hall. Two things happened to the study of popular culture as an interdisciplinary subject: (1) the study of popular culture has included wide range of issues (2) scholars have intellectual freedom in this field, and they show no interest in establishing clear boundaries around it. Popular culture is always defined in contrast to other conceptual categories such as folk culture, mass culture, dominant culture, and working class culture. Thus, popular culture becomes the 'Other' for them, which largely depends on the context of use. Lastly, the paper discusses the role of popular culture in history, anthropology, sociology and literary theories. In theory, the study of popular culture is always around the debate on postmodernism. It assumes that postmodern culture no longer recognizes the distinction between high culture and popular culture. Key Words: Popular culture; Romance novels; Science fiction; Photography; Pop music Tribhuvan University Journal Vol. XXVI, No. 1, 2009 Page: 27-36